Building Social Awareness in Elementary Madrasah Students through Understanding Population and the Indonesian Government System - Astina; Fia Alifah Putri; Wahyu Iskandar (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to examine the understanding of elementary school students regarding population and the Indonesian government system, and its impact on the formation of their social awareness. The problem studied is how citizenship education based on the topic of population and government systems can improve students' social awareness in elementary school. The research method used is a qualitative approach with a case study design, involving interviews, observations, and documentation in several elementary school in Kendari City. The research informants consisted of students, teachers, and principals. The data analysis technique used a thematic analysis model. The results of the study showed that a better understanding of population and the Indonesian government system was positively related to an increase in students' social awareness. Learning that integrates theory with real social experiences produces a more applicable understanding. As a result, students show higher social awareness, although there are gaps in the application of knowledge in everyday life. This study contributes to the development of more contextual and participatory citizenship learning methods, as well as encouraging changes in teaching practices in elementary school.